Pengembangan Modul Elektronik Teks Hikayat Berbasis Model Deduktif Kelas X SMA - Vioni Saputri (PAKAR Pendidikan, 2020)
The research was conducted to overcome the limitations of Indonesian language teaching materials. The purpose of this research is to explain the process and produce the product for the development of the electronic module for saga text learning based on the deductive learning model with valid, practical, and effective criteria to use. The research model used includes 4 stages, namely defining, designing, developing, and spreading. This research uses qualitative and quantitative data. The qualitative data were obtained from filling in two questionnaires, namely the validation of the electronic module and practicality and the sheet from making observations on student activities and student affective. Quantitative data were obtained based on student learning outcomes in saga text material. The results of this study indicate that the electronic module of saga text based on the deductive model is valid, practical, and effective. This is evidenced from the results of validity, practicality, and effectiveness. The practicality of the electronic module by teachers and students was 86.66% and 87.35% in the very practical category. The effectiveness of the electronic module based on the attitude aspect score is 92% with the predicate A and is categorized as very effective. The effectiveness of the electronic module based on student learning outcomes for the cognitive aspect is 90.24 with the A predicate and 86.64% for the aspect of developing saga in the form of short stories with the predicate A so that it is categorized as very effective.